GARRE’S OSTEOMYELITIS OF LONG BONE IN ADULT. - Khan, Amina Gul Shehzar; Haseeb Ahsin; Sajjad Khan; Waqar Hussain; Ansar Rafique; Ratib Kamal (Journal of Ayub Medical College Abbottabad, 2024)
Garre’s osteomyelitis is a rare form of chronic osteomyelitis characterized by sclerosing and periosteal reaction of the affected bone. We report a case of a 35-year-old woman who presented with left tibial pain and swelling for 18 months. She was diagnosed with Garre’s osteomyelitis of the mid-shaft tibia based on radiological and histopathological findings. She underwent curettage, biopsy and culture of the lesion, which revealed oxacillin-sensitive staphylococcus species. She was treated with targeted antibiotics and showed clinical improvement. This case highlights the importance of considering Garre’s osteomyelitis in the differential diagnosis of chronic tibial pain and the role of curettage and antibiotics in its management.